STUDY KOMPARATIF PSYCHOLOGICAL WELL-BEING MAHASISWA TINGKAT AWAL DAN TINGKAT AKHIR PADA BIMBINGAN DAN KONSELING UNIVERSITAS JAMBI - Willujeng Kurniati; K.A. Rahman; Hera Wahyuni (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
This study highlights that psychological well-being is a crucial aspect of college students' lives, particularly for those enrolled in Guidance and Counseling study programs. Final-year students demonstrated slightly higher levels of psychological well-being (70.04%) compared to first-year students (66.98%). However, statistical analysis revealed that this difference was not significant. This suggests that overall, psychological well-being does not significantly differ based on academic level. Nevertheless, these findings provide important insights into the unique psychological challenges faced by college students at each stage of their academic journey—from adaptation difficulties in the early years to academic and career stress in the later years. Therefore, higher education institutions need to develop targeted support services to meet the specific needs of students at each stage. Furthermore, this study contributes to the development of research on the psychological well-being of guidance and counseling students and provides a basis for designing more effective and developmentally appropriate interventions.